Analisis Struktur dan Makna Gerak Tari Gaya Zapin, Sarah, dan Zahefah Pada Seni Marawis di Pondok Pesantren Al Mubarokah Kabupaten Tasikmalaya - Nova Puspita; Asti Tri Lestari; Denden Setiaji (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
Marawis art is an Islamic art form that developed in Islamic boarding schools as a medium for da'wah and cultural education. The Marawis performance at the Al Mubarokah Islamic Boarding School in Tasikmalaya Regency features three dance styles, namely Zapin, Sarah, and Zahefah, which have movement structures and religious symbolic meanings. This study aims to analyze the movement structures and reveal the symbolic meanings of the Zapin, Sarah, and Zahefah styles in the Marawis Art performance. The study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. Data analysis was carried out through the stages of reduction, presentation, and drawing conclusions. The results of the study show that the movement structures of Zapin, Sarah, and Zahefah are syntagmatically structured as a unified whole performance, starting from dynamic movements, reflective transitions, to solemn movements. The meaning of the movements of the three styles represents the values ​​of togetherness, discipline, submission, and devotion to Allah SWT. Thus, the dance movements in Marawis Art function not only as aesthetic expression, but also as a medium for internalizing religious values ​​and character education for students in the Islamic boarding school environment.